Analisis Akuntabilitas Pengelolaan Dana Desa di Kadu Agung Kecamatan Gunungsari - Prihatin, Khristina Sri; Nurlaili, Fitri; Ilmi, Yusina Fadla; Mulyati, Budi (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2024)
Village Fund Management is one of the most important things in realizing the Vision and Mission of an area to improve the welfare of the community. The aim of this research is to find out an analysis of the accountability of village fund management in Kadu Agung, Gunungsari District, Banten Province. The research method used was qualitative by conducting direct observations and interviews with several employees and the community in Kadu Agung Village, Gunungsari District. Based on the results of research by conducting direct interviews, it shows that the village fund planning stages are in accordance with the regulations that have been implemented and only involve a few community leaders, but not all of them can be realized, the implementation stage has an implementation schedule and the realization is not entirely in accordance with the schedule even though the community has assisted. The accountability of Kadu Agung Village employees only has evidence in the form of receipts for purchasing goods and not the entire community knows about their accountability. The results of managing village funds in Kadu Agung are not in accordance with the needs and expectations of the community because many poor people do not receive assistance from the village, causing inequality between the community and the Kadu Agung Village.